Tretji prostori na univerzah - Žalac, Domen (Urbani izziv, 2024)
This article examines the potential of multifunctional university public spaces, or “third places”, with a particular focus on their role as catalysts for social interaction and urban development in the academic environment. It studies the University of Ljubljana’s Aškerc Street campus, which is undergoing complete urban regeneration. After identifying all the specific third places, the article shows why third places are important for various stakeholders (students and professors) and presents their suggestions on how to improve the third places on the campus. The findings show that, although university spaces are essential for academic and social activities, they have significant design and use limitations. It shows that students and faculty members frequently make use of third places on and off campus to study, work, relax, and socialize, and for other informal gatherings, and that there is a clear need to provide more flexible, accessible, and non-commercial spaces on the campus.
Keywords: Javne površine; javni prostori; Kampusi; multifunctional spaces; public spaces; third places; tretji prostori; university campus; univerzitetni kampus; urban development; urbanistični razvoj; Urbanizem; večnamenski prostori